Property management in real estate investment decision-making - Jaffe, Austin J. (Lexington, Mass. : Lexington Books, 1979)
Examination of the theoretical relationship between important variables found in the equity evaluation of real estate investment.
Includes index.
Includes bibliographical references: p. 137-153.
sju 22/01/2019
Loans
Keywords: Real estate investment - mathematical models